Assessment of sanitary status of food and drinks catering establishments: A descriptive observational study in south East Asmara, Eritrea, 2019 - Idris M Idris; Samuel J Wolday; Amanuel T Ghebremariam; Habtom Kidane; Misgina Leake; Hagos Milkias; Kahsay Ghebremichael (Archives of Community Medicine and Public Health - Peertechz Publications, 2020)
Objective: Lack of basic infrastructure, poor practices of hygiene in food service establishments can contribute to outbreaks of foodborne illnesses. The aims of this study was to explore the sanitary conditions of food and drink catering establishment services in South East Asmara, Eritrea.  Methods: A descriptive observational study was conducted among 139 food and drinks catering establishments in South East Asmara from June to September 2019. Data were collected using semi-structured questionnaire for obtaining socio-demographic information of the manager or owner and observation checklist was used to assess the overall physical sanitary status of the establishment. Factors influencing vermin infestation, kitchen and latrine cleanliness were further investigated. Data analysis was done using SPSS version 22. The descriptive results were summarized using frequencies and percentages in tables and graphs. Dining premises, kitchens and stores were categorized as clean, if the floor, wall, and ceiling of the premises were found clean. Moreover, bivariate and multivariate logistic regression analysis were done to find out the main factors influencing vermin infestation, kitchen and latrine cleanliness.  Results: Out of the total 139 food and drink catering establishments assessed, about one-tenth (8.6%) of the establishments' dining room, a third (33.3%) of the stores and 31.5% of the kitchens were in a poor and unclean sanitary conditions. Good premise floor status (AOR=18.03; 95%CI (2.09-155.1), P<0.05), availability of adequate light (AOR=5.02; 95%CI (1.01, 24.99), P<0.05), running water (AOR=0.26; 95%CI (0.09, 0.72), P<0.05) and dustbin availability (AOR=4.32; 95%CI (1.06, 21.6), P<0.05) were found having significant association with overall cleanliness of the kitchen. Two-third (65%) of the establishments' latrines were clean. Availability of separate latrine for male and female (AOR=2.34; 95%CI (1.06, 5.18), P<0.05), and separate latrine for clients and workers (AOR=3.41; 95%CI (1.10, 10.57) were the main factors potentiating latrine cleanliness. More than a third (37.4%) of the establishments were found to be infested by vermin. Nearer kitchen distance from latrine (AOR=3.65; 95%CI (1.60, 8.35), p<0.05), presence of pets (AOR=4.1; 95%CI (1.17, 14.40), and breeding of insects in the liquid waste disposal (AOR=4.08; 95%CI (3.37, 12.17), p<0.01) had significantly increased the presence of vermin infestation.  Conclusion: The sanitary condition of the food and drinks catering establishments in the study area was found to be poor.  There is a need to impose regulations and guidelines governing the basic sanitary requirement of the food and drinks catering establishments.